Systematic Literature Review Potensi Daun Ketepeng Cina (Cassia alata.L) Sebagai Antijamur Pada Dermatofitosis - Cahyani, Nur; Kusumawati, Dwi Endah (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Indonesia has a tropical climate suitable for fungal growth. Some fungal species are flora that can cause diseases in humans, for example dermatophytosis. The ketepeng cina plant (Cassia alata L.) is empirically known to have various medicinal properties. Some of its benefits include treating worms, canker sores, constipation, tinea versicolor, ringworm, scabies, and reducing itching. The part often used as medicine is the leaves. This study, a literature review, aims to find substances found in ketepeng cina leaves that have antifungal activity on dermatophytosis, which fungi cause dermatophytosis that are inhibited, and the antifungal mechanisms of ketepeng cina leaves. Methods:This study applies a systematic literature review method with data collection using the PRISMA approach (Primary Reporting System for Systematic Reviews and Meta-analyses). The search for articles in this study was conducted using the Google Scholar, ScienceDirect, and PubMed databases, and after analysis, six relevant articles were obtained. Results: The analysis results show that ketepeng cina leaf extract is able to inhibit the growth of Trichophyton rubrum, Trichophyton sp, Microsporum canis, and Malassezia globosa, fungi that cause dermatophytosis infections such as tinea pedis (athlete's foot), tinea cruris (eczema), tinea capitis (ringworm of the scalp) and tinea imbricata (ringworm / pile-up lesions). Conclusion: The active compounds that play a role in antifungal activity include anthraquinones, flavonoids, saponins, tannins, and terpenoids. The mechanism of action of these compounds includes damaging cell membranes, inhibiting the development of fungal hyphae, can suppress fungal growth, damaging fungal sterols which are the main layer of fungi, causing disruption of nutrient absorption needed for fungal growth, so that cells will enlarge and collapse, inhibiting the production of nucleic acids, proteins, and phospholipid membranes.